Current Perspectives on Epigenetic Modifications by Dietary Chemopreventive and Herbal Phytochemicals - Guo, Yue (Curr Pharmacol Rep, 2015)
Studies during the last two decades have revealed the involvement of epigenetic modifications in the development of human cancer. It is now recognized that the interplay of DNA methylation, post-translational histone modification, and non-coding RNAs can interact with genetic defects to drive tumorigenesis. The early onset, reversibility, and dynamic nature of such epigenetic modifications enable them to be developed as promising cancer biomarkers and preventive/therapeutic targets. In addition to the recent approval of several epigenetic therapies in the treatment of human cancer, emerging studies have indicated that dietary phytochemicals might exert cancer chemopreventive effects by targeting epigenetic mechanisms. In this review, we will present the current understanding of the epigenetic alterations in carcinogenesis and highlight the potential of targeting these mechanisms to treat/prevent cancer. The latest findings, published in the past three years regarding the effects of dietary phytochemicals in modulating epigenetic mechanisms will also be discussed.